2008
DOI: 10.1093/ajcn/88.3.677
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy density predicts women's weight change over 6 y

Abstract: Background Dietary energy density (ED) is positively associated with energy intake, but little is known about long-term effects on weight change. Objective We assessed whether dietary ED predicts weight change over 6 y among a sample of non-Hispanic, white women. Design Participants were part of a 6-y longitudinal study (n = 186), assessed at baseline and biennially. ED (in kcal/g) was calculated from the energy content of all foods (excluding beverages) with the use of three 24-h recalls. Height and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 41 publications
5
112
1
1
Order By: Relevance
“…This is indeed supported by two longitudinal studies, in which women on a HED diet gained more weight after 6-8 years than women on a LED diet. 28,29 Similarly, two long-term weight loss trials showed that weight loss in overweight and obese subjects was highest when the diet was low in energy density. 30,31 Because we provided all groups with the same amounts of energy, the LED groups received more foods in terms of weight and volume than HED groups.…”
Section: Discussionmentioning
confidence: 99%
“…This is indeed supported by two longitudinal studies, in which women on a HED diet gained more weight after 6-8 years than women on a LED diet. 28,29 Similarly, two long-term weight loss trials showed that weight loss in overweight and obese subjects was highest when the diet was low in energy density. 30,31 Because we provided all groups with the same amounts of energy, the LED groups received more foods in terms of weight and volume than HED groups.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four-hour dietary recall interviews were conducted by telephone at the Dietary Assessment Center at the Pennsylvania State University as described by Savage et al (15). Trained staff administered interviews with the use of the computerassisted Nutrition Data System for Research (NDS-R) software (database version 4.01_30; Nutrition Coordinating Center, University of Minnesota).…”
Section: Dietary Intakementioning
confidence: 99%
“…The NDS-R time-related database updates analytic data while maintaining nutrient profiles that are true to the bastion used for data collection. Reliability in interviewers is based on an interclass correlation $0.95 (15,16).…”
Section: Dietary Intakementioning
confidence: 99%
“…Besides total energy intake, dietary energy density (kcal/g) defined as the amount of energy in a given weight of food has received considerable attention in recent years as one of the main determinants of alarming obesity trends (WHO/FAO, 2003). Although some studies have failed to find any significant association between consumption of energy-dense diets and obesity (De Castro, 2004;Iqbal et al, 2006;Du et al, 2009), others have reported a significant positive association (Howarth et al, 2006;Ledikwe et al, 2006aLedikwe et al, , 2007Mendoza et al, 2007;Bes-Rastrollo et al, 2008;Savage et al, 2008). Such significant findings have also been confirmed by clinical trials, where reduction in dietary energy density has been resulted in significant weight loss (Ello-Martin et al, 2007).…”
Section: Introductionmentioning
confidence: 98%